DEVELOPMENT OF TOURISM IN VARIOUS FIELDS IN THE REPUBLIC OF UZBEKISTAN (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Tourism improves the lives of ordinary people, outstrips many industries in the world in terms of income. Natural resources, such as gas and oil, may be depleted, but it is difficult to say the same about tourism, of course, if we do not destroy tourist facilities ourselves lives.